2015
DOI: 10.2147/ott.s76526
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of ALDH2 rs671 polymorphism in esophageal cancer: evidence from 31 case-control studies

Abstract: BackgroundAldehyde dehydrogenase 2 (ALDH2), a critical enzyme for the detoxification of alcohol, is associated with many types of cancers. To verify the relationship of ALDH2 rs671 G>A polymorphism and esophageal cancer (EC), we performed a meta-analysis of a total of 31 published data including 8,510 patients and 16,197 controls.MethodsThe pooled odds ratio (OR) and the 95% confidence interval (CI) were calculated using a fixed or random-effects model. Heterogeneity (PH), publication bias, and sensitivity ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…non‐flushers were 1.02 (0.53, 1.99) among non‐ or light consumers (<200 g/week), 2.54 (1.64, 3.91) among moderate consumers (200–390 g/week) and 2.90 (1.82, 4.62) among heavy consumers (>390 g/week) . Several previous Chinese studies also showed increased EC risk associated with GA heterozygotes among non‐consumers or consumers of ≤30 g/d …”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…non‐flushers were 1.02 (0.53, 1.99) among non‐ or light consumers (<200 g/week), 2.54 (1.64, 3.91) among moderate consumers (200–390 g/week) and 2.90 (1.82, 4.62) among heavy consumers (>390 g/week) . Several previous Chinese studies also showed increased EC risk associated with GA heterozygotes among non‐consumers or consumers of ≤30 g/d …”
Section: Discussionmentioning
confidence: 91%
“…The rs671 GA heterozygotes were linked to an increased EC risk (OR = 2.34; 95% CI: 1.75, 3.13) in a recent meta‐analysis of 31 case–control studies, almost exclusively conducted in China and Japan . The OR (95% CI) of GA heterozygotes for EC was 1.21 (0.95, 1.73) among non‐alcohol consumers, 3.79 (3.04, 4.72) among light consumers (1–350 g/week of alcohol) and 6.50 (5.34, 7.92) among heavy consumers (≥350 g/week of alcohol).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In site-specific studies, potential linkages of the ALDH*2 genotype to colorectal, stomach, pancreatic, breast, and head and neck cancers have been suggested. A subset of these sitespecific cancers have been further investigated via meta-analyses [48][49][50]. Nonetheless, weak associations and study limitations prevent sweeping conclusions regarding the role(s) of ALDH2*2 inheritance in cancer risk.…”
Section: Diseases Associated With the Inheritance Of Aldh2*2mentioning
confidence: 99%
“…The genetic background of residents from high- and low-incidence areas for both GCA and ESCC may be different. Previous reports including our GWAS studies show that alcohol drinking interacted with ALDH2 (rs671) on ESCC susceptibility 7,32,33 . Owing to the similar underlying molecular mechanism involved in both GCA and ESCC, the researchers found that the rs671 variation might interact with alcohol consumptions on GCA susceptibility.…”
Section: Discussionmentioning
confidence: 54%